Pengaruh Kepatuhan Konsumsi Tablet Fe terhadap Kadar Hb Ibu Hamil di Puskesmas Johan Pahlawan, Kabupaten Aceh Barat - Mardhiah, Mardhiah; Muliadi, Teuku; Anwar, Sufyan; Putri, Suci Eka (Medan Resource Center, 2024)
Anemia remains a significant global health concern, with the World Health Organization (WHO) reporting a prevalence of 29.9% in 2023. Among pregnant women aged 15–49, anemia affects over half a billion individuals, potentially leading to complications such as preterm birth, low birth weight, and developmental disorders due to inadequate iron reserves in newborns. Despite efforts at the Johan Pahlawan Health Center to distribute Fe tablets to 921 pregnant women, cases of low hemoglobin (Hb) levels persist. This study aims to examine the relationship between compliance with Fe tablet consumption and Hb levels in pregnant women. Using an analytical survey with a cross-sectional approach, data were collected from 48 pregnant women in May 2024. Chi-Square statistical analysis revealed a significant association between Fe tablet adherence and Hb levels, with a p-value of 0.024. These findings indicate that adherence to Fe tablet consumption correlates with improved Hb levels among pregnant women in the Johan Pahlawan Health Center's working area. Future studies are encouraged to explore the impact of high-iron dietary intake on maternal weight gain during pregnancy to provide a comprehensive understanding of maternal nutrition.